Strategic planning for national knowledge-based development using the SWOT strategic model - Mehdi Jamalinejad; Ali Zangiabadi; Hamid Reza Varesi (Management Science Letters)
Industrialized and rich nations owe much of their development to advances and achievements they have made in science and technology. These assets have not only served as engines powering their advanced economies but have also led to their exponential social growth. Thus, advancements in science and technology may be regarded as indicators of fundamental development in any modern society as it is the knowledge-based society that is in a superior position to address and resolve its basic problems. While Iran has also been taking drastic steps towards its scientific and technological development, decisive measures are yet to be taken toward developing a strategic plan for these development objectives and gaining a comprehensive understanding of its different aspects. Employing an analytic-descriptive approach, the present study aims to develop fundamental strategies for the national scientific and technological development using the SWOT strategic model. The results indicate that the development of infrastructure for access to information networks with a weight of 0.56 ranks first among the strengths while absence of a strategic development plan with a weight of 0.372 ranks first among the weaknesses. IT infrastructure with a weight of 0.608 is found to have the highest weight among the opportunities while the low relevance between educational programs (at both levels of general and higher education) and scientific and innovation requirements is found to rank first with a weight of 0.46 among the threats. Among the most essential strategies that need to be adopted, one can refer to the development of a basic framework for the uniform and need-oriented connectivity and access to IT and the Internet across the nation; creation and development of such knowledge-based systems and facilities as business and technology incubators, science parks, science a& technology corridors, and innovation clusters aiming at a knowledge-based, dynamic, and developed society; directing efforts at striking a balance between the number of university graduates and the market demands for young educated work force; and maximum involvement of the educated youths in the realization of national development objectives.